2002
DOI: 10.1063/1.1494123
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance study of interface defects in atomic layer deposited hafnium oxide on Si

Abstract: We report electron spin resonance ͑ESR͒ observation of interface defects at the HfO 2 /(111)Si boundary for HfO 2 films deposited via atomic layer chemical vapor deposition using Hf(NO 3) 4 as a precursor. We observe several signals, dominated by one due to a silicon dangling bond at the Si/dielectric interface. This center is somewhat similar to, but not identical to, Si/SiO 2 interface silicon dangling bonds. Comparison between ESR and capacitance versus voltage measurements suggests that these dangling bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…However, the peak locations in the band-gap are not precisely the energies expected for P b0 centers [1,2,10]. This is consistent with several electron spin resonance studies which have shown that interface defects in Si/SiO 2 /HfO 2 gate stacks are very similar but not quite identical to the Si/SiO 2 P b0 centers [11][12][13]. Thus, it is reasonable to assume that interface defects in the HfO 2 based gate stack will have a different density of states distribution.…”
Section: The Second Bulk Trap Effect Is Due To Trapped Charge Inducedsupporting
confidence: 86%
“…However, the peak locations in the band-gap are not precisely the energies expected for P b0 centers [1,2,10]. This is consistent with several electron spin resonance studies which have shown that interface defects in Si/SiO 2 /HfO 2 gate stacks are very similar but not quite identical to the Si/SiO 2 P b0 centers [11][12][13]. Thus, it is reasonable to assume that interface defects in the HfO 2 based gate stack will have a different density of states distribution.…”
Section: The Second Bulk Trap Effect Is Due To Trapped Charge Inducedsupporting
confidence: 86%
“…9 This feature can be reduced by a forming gas anneal at 400°C. 5,7 A profile of the density of states ͑DOS͒ across the full energy gap for a hydrogen free interface of Au/HfO 2 /Si(100) structures reveal an interface state profile very similar to that measured for the hydrogen-free thermally oxidized Si(100)/SiO 2 system, but with a factor of two to three increase in defect density. 10 The purpose of this article is to build on these previous publications, with the aim of investigating if the frequency dependent kink commonly observed in the capacitancevoltage characteristics of high-MOS structures can be linked to the density of P b centers measured by ESR, with a view to providing atomic identification for the defects responsible for the observed atypical CV effects.…”
mentioning
confidence: 77%
“…2 In relation to the electrical activity of the interface defects in the Si͑100͒/high-system, it has been reported that capacitance-voltage ͑CV͒ characteristics have a nonideal behavior, with a frequency-dependent feature in the region between accumulation and strong inversion for ZrO 2 and HfO 2 MOS structures. [5][6][7][8][9] Modeling of the CV characteristics of this frequencydependent feature over n-type silicon, reveals a peak at 0.82 eV from the valence band edge, whose capture cross-section and location are independent of measurement frequency. 9 This feature can be reduced by a forming gas anneal at 400°C.…”
mentioning
confidence: 99%
“…This hump, together with the stretch-out of the C±V curves, has been observed in HfO 2 and ZrO 2 films on silicon, [31,32] and arises from the capacitive response of fast interface states, in particular dangling Si bonds, i.e., P b centers. [33,34] Forming gas annealing is known to passivate dangling bonds, [35] thereby reducing the interface state density. Indeed, the hump vanished, and the slope of the C±V curves around the flat-band voltage increased significantly, after a forming gas anneal at 400 C (Fig.…”
Section: Dielectric Propertiesmentioning
confidence: 99%